Perancangan Prototype Pelampung Keselamatan Elektrik dengan Algoritma Proportional Integral Derivative Untuk Kestabilan di Air - Kusrini, Kusrini; Pramono, Eko; Muktafin, Elik Hari; Setiaji, Bayu; Putra, Andriyan Dwi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This research addresses the need for a water rescue device capable of autonomously moving towards a survival position while being remotely controlled. The main problem investigated is how to design an electric safety buoy that can move stably in currents and waves while being operated remotely using Internet of Things (IoT) technology. Data were collected through prototype testing under various load and control range conditions. The research method involves designing and implementing a control system based on the Arduino Uno microcontroller, with a Proportional-Integral-Derivative (PID) algorithm to maintain buoy stability, and an RF communication module for remote control up to 500 meters. The test results show that the buoy can achieve an average speed of 1.35 m/s at 100% throttle with an 80 kg load and maintain stability in various water conditions. The standard deviation of speed indicates minimal variation between tests, demonstrating good movement stability. This research contributes to the development of IoT-based safety devices, enhancing the effectiveness of water rescue operations. With the use of a PID algorithm, the buoy can automatically adjust direction and speed, making it more responsive to remote control commands and able to withstand dynamic water conditions.